DEVELOPMENT OF FUNDAMENTAL MOTOR SKILLS IN READINESS STATE FOR ALPHABETIZATION: A COMPARISON WHITH 6-YEAR-OLD STUDENTS (Fiep Bulletin - online, 2013)
This study aimed to compare six-year- old students who didn't undergo infantile education to students who, at least, had a one-year infantile education, in terms of their fundamental motor ability development and their “promptitude” for literacy. 20 (twenty) students aged six years old, both male and female, took part in the study and, among them, seven didn't undergo infantile education. In order to evaluate the fundamental motor abilities, Gallahue and Ozmun test ( 2003 ) was used, correspondent to the age of six years old, through six chosen abilities in a convenient way: dynamic equilibrium, jump, kick, run, throw and catch. To evaluate the students' promptitude for literacy, the “R Type Promptitude Test” ( TMP ) by Hildret and Griffiths was used with adaptation and standardization by Poppovic ( 1966 ). Through the obtained results, it's noticed a direct relation between psycho-motor education and “promptitude” for literacy, that means, students who underwent infantile education had “medium” ( 9 students ), “superior” ( 3 students ) and “medium-inferior” ( only one student ) classifications regarding their promptitude for literacy according to the TMP test. Poppovic analyses the only “medium-inferior” classification as a consequence of a slower degree of maturity and/or emotional reasons. These same students were placed in the “elementary” and “mature” phases. Students who didn't undergo infantile education were placed in the TMP test, in the “inferior” and “medium-inferior” classifications and in the Fundamental Motor Ability Test they presented more than one ability in the initial phase.
Keywords: psycho-motory; promptitude and Literacy